2015
DOI: 10.1016/j.neurobiolaging.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

An anti-pyroglutamate-3 Aβ vaccine reduces plaques and improves cognition in APPswe/PS1ΔE9 mice

Abstract: Pyroglutamate-3 amyloid-beta (pGlu-3 Aβ) is an N-terminally truncated Aβ isoform likely playing a decisive role in Alzheimer's disease (AD) pathogenesis. Here, we describe a prophylactic passive immunization study in APPswe/PS1ΔE9 mice using a novel pGlu-3 Aβ IgG1 monoclonal antibody (mAb), 07/1 (150 and 500μg i.p. weekly), and compare its efficacy with a general Aβ IgG1 mAb, 3A1 (200μg i.p. weekly) as a positive control. After 28 weeks of treatment, plaque burden was reduced and cognitive performance of 07/1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 76 publications
(102 reference statements)
4
54
0
Order By: Relevance
“…The platform is a 5 cm x 5 cm square made from Plexiglas and was submerged during the experiments. A recent study has been published using this behavioral paradigm (Frost et al, 2015). Mice were given 10 trials per day with an inter-trial interval (ITI) of approximately 5–8 min.…”
Section: Methodsmentioning
confidence: 99%
“…The platform is a 5 cm x 5 cm square made from Plexiglas and was submerged during the experiments. A recent study has been published using this behavioral paradigm (Frost et al, 2015). Mice were given 10 trials per day with an inter-trial interval (ITI) of approximately 5–8 min.…”
Section: Methodsmentioning
confidence: 99%
“…Another study revealed that unlike the non‐pyroglutamated Aβ load, the Aβ 3(pE) load correlates with both AD severity and the amount of hyperphosphorylated tau, suggesting that Aβ 3(pE) may represent a missing link between Aβ and tau pathologies . Passive immunotherapy with a monoclonal antibody designed to specifically target Aβ 3(pE) , effectively lowered not only cerebral Aβ plaque burden but also reversed cognitive decline in a Tg mouse model . Thus, N‐terminally truncated and pyroglutamated Aβ, in particular Aβ 3(pE)–42 , may not be just a byproduct of Aβ deposition into plaques but may actually play a central role in AD pathology.…”
Section: Aβ and Its Role In Alzheimer's Diseasementioning
confidence: 99%
“…pGlu-A␤ exhibits increased aggregation propensity and increased cellular toxicity and disrupts long term potentiation to a greater extent than A␤1-X species (39 -41). In addition, recent work has proposed pGlu-A␤ as the predominant A␤ species within the brains of AD patients (42), and efforts to design therapeutics specifically targeting this A␤ species have proved successful in mouse models (43). However, evidence for direct proteolysis of APP between Ala 673 -Glu 674 by cathepsin B remains to be provided.…”
Section: Cathepsin Bmentioning
confidence: 99%